An Improved A Low Power CMOS TIQ Comparator Flash ADC - A Al; Mamun B. Ibne Reaz; J. Jalil; Mohd. Alauddin Bin Mohd. Ali (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This paper was presented the design of a threshold inverter quantized (TIQ) comparator in flash analog to digital converter. The TIQ-comparator has a high speed response; however this circuit involves a lot of transistors hence wasteful power consumption. The design is intended to obtain a low-power TIQ-comparator and reduces the area of the chip in 0.18 µm CMOS technology. The method was proposed to set each of the transistor channel length for the threshold voltage difference gained of the inverter each in the TIQ-comparator and adding a transistor as compensation to overcome the limitations of the length channel expansion due to the body effect influence. This method has reduced the drain current of CMOS transistors; hence the power dissipation can be reduced. The event has achieved low power dissipation of 31.14 µW and a chip size of 1065 µm2 with 0 to 0.6 V input signal condition.